Non-sticking wheel modified emulsified asphalt and preparation method thereof

By preparing non-stick modified emulsified asphalt, the problems of easy sticking to wheels and low construction efficiency of modified asphalt under high temperature conditions were solved, improving the stability and construction efficiency of asphalt pavement, and enhancing shear strength and pull-out resistance.

CN120365588APending Publication Date: 2025-07-25西安市政道桥建设集团有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510735976.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-04
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

Existing modified asphalt tends to stick to wheels under high-temperature conditions, resulting in low construction efficiency and poor stability, making it difficult to meet the requirements for use on long longitudinal slopes and in high-temperature environments.

Method used

Non-stick modified emulsified asphalt was prepared by mixing anti-rutting masterbatch with asphalt matrix and keeping it at a constant temperature in an oven, combined with emulsifier, stabilizer and acid solution treatment. The emulsification process and cooling treatment were controlled to improve stability.

Benefits of technology

It achieves stability and construction efficiency of modified asphalt under high temperature conditions, reduces wheel adhesion rate, and improves the structural bearing capacity and service performance of asphalt pavement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120365588A_ABST
    Figure CN120365588A_ABST
Patent Text Reader

Abstract

The invention discloses wheel-sticking-free modified emulsified asphalt and a preparation method thereof, and relates to the technical field of asphalt modification.The method comprises the steps that anti-rutting master batches and an asphalt matrix are mixed and ground to obtain modified asphalt, and the modified asphalt is placed in a constant-temperature drying oven to be subjected to heat preservation to a first temperature; wherein the mixing amount of the anti-rutting master batch is 25%-40%; mixing an emulsifier, a stabilizer and water, heating and stirring to obtain an emulsion at a second temperature; adding an acidic solution into the emulsified liquid until the pH value of the emulsified liquid is adjusted to a set pH value range; and pouring the emulsified liquid into a colloid mill, and pouring the modified asphalt at the first temperature into the colloid mill to obtain the non-sticking wheel modified emulsified asphalt. The technical problems that in the prior art, modified asphalt is poor in use performance and low in construction efficiency are solved. The non-sticking wheel modified emulsified asphalt is convenient to construct and good in stability and shear strength, the bearing capacity of an asphalt pavement structure can be improved, the use performance of an asphalt pavement is improved, and the service life of the pavement is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of asphalt modification, and particularly to a non-sticking wheel modified emulsified asphalt and a preparation method thereof. Background Art

[0002] There are various types of tack coat materials commonly used on the market for asphalt pavements, including cut-back asphalt, ordinary hot asphalt, modified asphalt, ordinary emulsified asphalt, and modified asphalt. The diluents added to cut-back asphalt will have an adverse impact on the underlying layer or base course and will also pollute the environment. The bonding performance of ordinary hot asphalt is poor and cannot provide sufficient bonding strength, resulting in limited effectiveness in practical applications. Modified asphalt needs to be sprayed at high temperatures, making the construction difficult. The stability of ordinary emulsified asphalt is poor and it is prone to deformation at high temperatures, unable to ensure sufficient bonding strength.

[0003] Currently, modified asphalt is a hot topic in the research of tack coat materials, and most of them adopt SBR (styrene-butadiene rubber) modification technology, which has low requirements for equipment and a simple preparation process. However, under some specific conditions, such as long uphill and downhill sections, emergency braking of vehicles, high temperatures, etc., modified asphalt is difficult to meet the actual use requirements. The softening point of modified asphalt is usually below 60°C. During the actual construction process, after the modified asphalt breaks emulsification, due to the high temperature of the road surface, especially when the road surface temperature is often greater than 60°C during summer construction, which exceeds the softening point of the modified asphalt tack coat. When vehicles drive and roll over this road surface, the phenomenon of sticking wheels will occur, and the tack coat of the road surface will also be damaged, resulting in a reduction in the service performance of the asphalt pavement. In addition, the demulsification and curing time of modified asphalt is relatively long, usually waiting for several hours before the next layer of mixture can be paved, resulting in low construction efficiency. Summary of the Invention

[0004] The embodiments of this application provide a non-sticking wheel modified emulsified asphalt and a preparation method thereof, which solve the technical problems of poor service performance and low construction efficiency of modified asphalt in the prior art.

[0005] In a first aspect, the embodiments of this application provide a preparation method of a non-sticking wheel modified emulsified asphalt, including: mixing a rutting resistance masterbatch with an asphalt matrix and grinding to obtain modified asphalt, and placing the modified asphalt in a constant temperature oven to keep it at a first temperature; wherein, the dosage of the rutting resistance masterbatch is 25%-40%; mixing an emulsifier, a stabilizer and water, and heating and stirring to obtain an emulsion at a second temperature; adding an acidic solution to the emulsion until the pH of the emulsion is adjusted to a set pH range; pouring the emulsion into a colloid mill, and slowly pouring the modified asphalt at the first temperature into the colloid mill to obtain a non-sticking wheel modified emulsified asphalt.

[0006] In combination with the first aspect, in a possible implementation manner, the first temperature is 170°C.

[0007] In combination with the first aspect, in a possible implementation, the second temperature is 65 - 70 °C.

[0008] In combination with the first aspect, in a possible implementation, the set pH range is 2 - 3.

[0009] In combination with the first aspect, in a possible implementation, the acidic solution is a hydrochloric acid solution.

[0010] In combination with the first aspect, in a possible implementation, slowly pouring the modified asphalt at the first temperature into the colloid mill further includes: when the color of the emulsion in the colloid mill changes, increasing the pouring speed of the modified asphalt.

[0011] In combination with the first aspect, in a possible implementation, the stabilizer includes Shanxi emulsified asphalt enhancer and HVS asphalt stabilizer; when the dosage of the rutting resistance masterbatch is 40%, the dosage of the Shanxi emulsified asphalt enhancer is 0.2%; when the dosage of the rutting resistance masterbatch is 20% - 30%, the dosage of the Shanxi emulsified asphalt enhancer is 0.1%; the dosage of the HVS asphalt stabilizer is 0.2%.

[0012] In combination with the first aspect, in a possible implementation, mixing the emulsifier, the stabilizer and water includes: the emulsifier is E106, and when adding the emulsion to prepare the non-sticking wheel modified emulsified asphalt, the dosage of the emulsifier is 6%.

[0013] In combination with the first aspect, in a possible implementation, after obtaining the non-sticking wheel modified emulsified asphalt by mixing, it further includes: rapidly cooling the non-sticking wheel modified emulsified asphalt to prevent the non-sticking wheel modified emulsified asphalt from demulsifying at high temperature.

[0014] In the second aspect, an embodiment of the present application provides a non-sticking wheel modified emulsified asphalt prepared by the method according to the first aspect or any one of the possible implementation manners of the first aspect, including: the spraying amount of the non-sticking wheel modified emulsified asphalt is 0.7 kg / m 2 , and the construction temperature is 60 °C.

[0015] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages: In the embodiment of the present application, by placing the modified asphalt in a constant-temperature oven and keeping it at the first temperature, the emulsification rate of the asphalt can be ensured; adding an emulsifier can improve the storage stability of the non-sticking wheel modified emulsified asphalt; effectively solving the technical problems of poor use performance of the modified asphalt in the prior art and low construction efficiency. A non-sticking wheel modified emulsified asphalt that is convenient for construction, has good stability and shear strength is realized. Its tensile strength is less affected by temperature changes, and the asphalt adhesion rate after wheel rolling is small, thereby being able to improve the bearing capacity of the asphalt pavement structure, improve the use performance of the asphalt pavement and extend the service life of the pavement. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings required for use in the description of the embodiments of the present application or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0017] Figure 1 It is a flowchart of a preparation method of a non-sticking wheel modified emulsified asphalt provided by an embodiment of the present application; Figure 2 It is a relationship diagram between the content of the anti-rutting masterbatch and the softening point of the modified asphalt provided by an embodiment of the present application; Figure 3 It is a relationship diagram between the content of the anti-rutting masterbatch and the penetration of the modified asphalt provided by an embodiment of the present application; Figure 4 It is a comparison diagram of the pull-out strength of six different formulations of non-sticking wheel modified emulsified asphalt at different temperatures provided by an embodiment of the present application; Figure 5 It is a comparison diagram of the pull-out strength of six different formulations of non-sticking wheel modified emulsified asphalt under three spraying amounts provided by an embodiment of the present application; Figure 6 It is a comparison diagram of the direct shear test results of asphalt with different schemes provided by an embodiment of the present application; Figure 7 It is a bar chart of the adhesion rate of different interlayer bonding materials when rolling 1 round trip provided by an embodiment of the present application; Figure 8 It is a bar chart of the adhesion rate of different interlayer bonding materials when rolling 5 round trips provided by an embodiment of the present application; Figure 9 It is a bar chart of the adhesion rate of different interlayer bonding materials when rolling 10 round trips provided by an embodiment of the present application; Figure 10 It is a bar chart of the adhesion rate of different interlayer bonding materials when rolling 20 round trips provided by an embodiment of the present application; Figure 11Adhesion rate curve graphs of four different solutions provided by embodiments of this application at different temperatures. Detailed implementation manners

[0018] The following will clearly and completely describe the technical solutions in the embodiments of this application with reference to the accompanying drawings in the embodiments of this application. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0019] The following explanations are made for some technologies involved in the embodiments of this application to facilitate understanding. It should be considered that they are merely exemplary. Therefore, those of ordinary skill in the art should recognize that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of this application. Similarly, for the sake of clarity and conciseness, some descriptions of well-known functions and structures are omitted in the following description.

[0020] Figure 1 is a flowchart of a preparation method of a non-stick wheel modified emulsified asphalt provided by an embodiment of this application, including steps 101 to 104. Among them, Figure 1 This is only an execution order shown in the embodiments of this application and does not represent the only execution order of a preparation method of a non-stick wheel modified emulsified asphalt. Under the condition that the final result can be achieved, Figure 1 the steps shown can be executed in parallel or reversed.

[0021] Step 101: Mix the rutting-resistant masterbatch with the asphalt matrix and grind to obtain modified asphalt, and place the modified asphalt in a constant-temperature oven to keep warm to the first temperature. In the embodiments of this application, the first temperature is 170°C.

[0022] Specifically, use a high-speed shearer to shear the rutting-resistant masterbatch and mix it with the asphalt matrix for modification to obtain modified asphalt, and then place the mixed modified asphalt in a constant-temperature oven to keep warm to 170°C.

[0023] Step 102: Mix the emulsifier, stabilizer and water, and heat and stir to obtain an emulsion at the second temperature. In the embodiments of this application, the acidic solution is hydrochloric acid solution, and the second temperature is 65 - 70°C. The stabilizer includes Shanxi emulsified asphalt enhancer and HVS asphalt stabilizer. When the dosage of the rutting-resistant masterbatch is 40%, the dosage of Shanxi emulsified asphalt enhancer is 0.2%. When the dosage of the rutting-resistant masterbatch is 20% - 30%, the dosage of Shanxi emulsified asphalt enhancer is 0.1%, and the dosage of HVS asphalt stabilizer is 0.2%. The emulsifier of this application is exemplarily E106 emulsifier. Mix the emulsifier with water and heat and stir to 65 - 70°C to obtain an emulsion. The water used here is clean tap water.

[0024] Step 103: Add an acidic solution to the emulsion until the pH of the emulsion is adjusted to the set pH range. In the embodiment of the present application, the set pH range is 2 - 3. The emulsifier is E106. When preparing the non-stick wheel modified emulsified asphalt and adding it to the emulsion, the dosage of the emulsifier is 6%.

[0025] Specifically, after the emulsifier in the emulsion is completely melted into the water, add hydrochloric acid solution to adjust the pH value of the emulsion until the pH value is 2 - 3.

[0026] Step 104: Pour the emulsion into a colloid mill, and slowly pour the modified asphalt at the first temperature into the colloid mill to obtain the non-stick wheel modified emulsified asphalt. In the embodiment of the present application, when the color of the emulsion in the colloid mill changes, the pouring speed of the modified asphalt is increased.

[0027] Specifically, add tap water to the colloid mill in advance to clean and heat up the colloid mill, and then control the temperatures of the emulsion and the modified asphalt. The temperature of the emulsion is controlled at 70°C, and the temperature of the modified asphalt is controlled at 170°C. Add the 70°C emulsion to the colloid mill, and then slowly pour the 170°C modified asphalt. This process is kept slow. After the color of the emulsion in the colloid mill changes, the pouring speed of the modified asphalt can be slightly increased. If the speed is too slow, it will be difficult to emulsify the modified asphalt after it cools down. The speed should not be too fast either. The modified asphalt is relatively viscous, and if the addition speed is too fast, it is easy to cause the colloid mill to get stuck. After mixing evenly, the non-stick wheel modified emulsified asphalt is obtained.

[0028] The temperature of the prepared non-stick wheel modified emulsified asphalt finished product is relatively high. After successful emulsification, the non-stick wheel modified emulsified asphalt needs to be quickly cooled to prevent the emulsified asphalt from demulsifying due to excessive temperature.

[0029] In the embodiment of the present application, the non-stick wheel modified emulsified asphalt is quickly cooled to prevent the non-stick wheel modified emulsified asphalt from demulsifying at high temperature.

[0030] The present application also provides a non-stick wheel modified emulsified asphalt prepared by the above method. The spraying amount of the non-stick wheel modified emulsified asphalt is 0.7 kg / m 2 , and the construction temperature is 60°C.

[0031] Through the following tests, study the proportions of various materials when preparing the non-stick wheel modified emulsified asphalt and the performance of the non-stick wheel modified emulsified asphalt. Different dosages of anti-rutting masterbatches can be added to the asphalt matrix to prepare hard asphalt with different performances. As the dosage of the anti-rutting masterbatch increases, the softening point of the hard asphalt increases, the penetration decreases, the ductility attenuates, and the larger the dosage, the more difficult it is to emulsify the hard asphalt. According to the requirements of the "Technical Guide for Non-Stick Wheel Emulsified Asphalt Tack Coat Treatment", the softening point of the evaporation residue of the emulsified asphalt shall not be lower than 75°C.

[0032] In one embodiment of the present application, antirutting masterbatches with five dosages of 20%, 25%, 30%, 40%, and 50% are respectively added and mixed with the asphalt matrix. Under each dosage condition, the antirutting masterbatch and the asphalt matrix are sheared at high speed for 1 hour to prepare modified asphalt with different hardnesses.

[0033] During the emulsification process of various hard modified asphalts, the E106 emulsifier is used for emulsification, and the emulsification difficulty of modified asphalts with different hardnesses is analyzed by comparison. The higher the softening point of the asphalt, the more beneficial it is to achieve the effect of non-sticking wheels. The test results of the emulsification points of modified asphalts with different dosages of antirutting masterbatches are as Figure 2 shown. From Figure 2 it can be seen that the antirutting masterbatch has a significant effect on improving the softening point of the modified asphalt. When the dosage reaches more than 20%, the softening point of the modified asphalt can be higher than 60 °C. When the dosage is greater than 40%, the softening point of the modified asphalt can reach more than 75 °C.

[0034] The value of the penetration reflects the hardness of the asphalt. The change in the penetration of modified asphalts with different proportions of antirutting masterbatches added is as Figure 3 . From Figure 3 it can be known that adding the antirutting masterbatch has a significant effect on reducing the penetration of the modified asphalt. When 30% of the antirutting masterbatch is added, the penetration of the modified asphalt drops to about 12 mm. This is because the content of the heavy components in the antirutting masterbatch is relatively high. The content of the light components in the modified asphalt prepared therefrom decreases, the content of the colloid and asphaltene increases, and the viscosity also increases, resulting in the decrease of its penetration.

[0035] Four emulsifiers, namely E106 (referring to riboflavin-5'-phosphate sodium), 1319 (a commodity number of polyoxyethylene sorbitan monooleate), M55 (a composite emulsifier), and M16 (a composite emulsifier), are respectively selected. The asphalt matrix is XinHai 70# asphalt (70# asphalt produced by Hebei XinHai Chemical Industry Group Co., Ltd.) with a dosage of 60%, the dosage of the antirutting masterbatch is 40%, the ratio of water to the modified asphalt is 50:50, and the stabilizer is selected as the inorganic stabilizer CaCl2 with a ratio of 0.2% of the modified asphalt. The pH value of the emulsion is between 2 and 3. The dosages of the four emulsifiers are all in accordance with the recommended optimal dosages in the product instructions.

[0036] The emulsification effects of different emulsifiers are evaluated according to the success or failure of the emulsification of the non-sticking wheel modified emulsified asphalt, the residue on the 0.18 mm sieve, and the 1-day storage stability of the emulsion. The test results are shown in Table 1 below.

[0037] Table 1 Comparison table of emulsification effects of different emulsifiers

[0038] According to the results in Table 1, the 1319 emulsifier is not suitable for the non-stick wheel modified emulsified asphalt system. In Test Plans 2, 4, and 7, obvious oil-water separation occurred in the non-stick wheel modified emulsified asphalt after standing overnight, and asphalt similar to a sponge with more pores formed on the surface, resulting in emulsification failure. In addition, the M16 emulsifier cannot be used alone and needs to be compounded with other emulsifiers. According to the requirements of the "Construction Technical Guide for Non-Stick Wheel Emulsified Asphalt Tack Coat", the emulsified asphalt material should meet the following key performance indicators: the standard sieve residue on a 0.18 mm sieve hole of its evaporation residue should not be greater than 0.1%, and at the same time its 1-day storage stability should not be greater than 1%. In Test Plans 5, 6, and 8, although the sieve residue and 1-day storage stability meet the requirements, the relatively high emulsifier dosage leads to an increase in cost, and the emulsified asphalt is too viscous, which will increase the difficulty of the construction spraying process. The E106 emulsifier can emulsify the modified asphalt well, and the non-stick wheel modified emulsified asphalt prepared has the best fluidity, with less emulsifier dosage and low cost.

[0039] Stabilizer A (Shanxi emulsified asphalt enhancer, an additive used to enhance the performance of emulsified asphalt, and its main component is a bio-based emulsification enhancer) and Stabilizer B (HVS asphalt stabilizer, a chemical additive specially used to improve the performance of asphalt) were respectively selected, and the L 9 (3^ 4 ) orthogonal test design was used for the test. The test factors and combinations of the orthogonal design are shown in Tables 2 and 3, where the dosage of the rutting resistance masterbatch was adopted by the internal admixture method. The orthogonal test tables of the non-stick wheel modified emulsified asphalt with the two stabilizers added are shown in Tables 4 and 5.

[0040] Table 2 Test Factors and Combinations with Stabilizer A

[0041] Table 3 Test Factors and Combinations with Stabilizer B

[0042] Table 4 Orthogonal Test Table of Non-Stick Wheel Modified Emulsified Asphalt with Stabilizer A Added

[0043] Table 5 Orthogonal Test Table of Non-Stick Wheel Modified Emulsified Asphalt with Stabilizer B Added

[0044] In this application, to determine the best formula of the non-stick wheel modified emulsified asphalt, the softening point of the evaporation residue, penetration, 1-day storage stability of the emulsion, and 5-day storage stability were selected as evaluation indicators. The performance test results of the non-stick wheel modified emulsified asphalt with the two stabilizers added are shown in Tables 6 and 7 respectively.

[0045] Table 6 Performance test results of non-stick wheel modified emulsified asphalt with stabilizer A added

[0046] Table 7 Performance test results of non-stick wheel modified emulsified asphalt with stabilizer B added

[0047] According to the analysis of the test results in the above Tables 2 to 7, the evaporation residue and penetration test results of non-stick wheel modified emulsified asphalt with different formulations with stabilizer A added are shown in Table 8. The requirement for the penetration of non-stick wheel emulsified asphalt in the "Technical Guide for the Construction of Non-stick Wheel Emulsified Asphalt Tack Coat" is 0 - 40, and all the schemes in Table 8 meet the requirements.

[0048] Table 8 Penetration results of evaporation residue of non-stick wheel modified emulsified asphalt

[0049] Table 9 Analysis of variance table for penetration results of evaporation residue

[0050] The analysis of variance was carried out on the test results of the penetration of different schemes in Table 8, and the results are shown in Table 9. Among them, R 2 = 0.998, < 0.05 (the probability that the result is caused by random error is less than 5%), < 0.01 (the result is more reliable, and the random error probability is less than 1%). R 2 represents the coefficient of determination, and its value range is 0 - 1. The closer it is to 1, the stronger the linear relationship between the independent variable and the dependent variable. F in Table 9 represents the ratio of the between-group variance to the within-group variance. The larger the value of F, the more significant the between-group difference. It can be seen from Table 9 that the dosage of the rutting resistance masterbatch has a significant impact on the penetration of the evaporation residue, while the dosages of the emulsifier and stabilizer A have less impact. From the values of F and the significance values, the influence effects of the three factors are: dosage of rutting resistance masterbatch > dosage of emulsifier > dosage of stabilizer A.

[0051] The penetration test results of the evaporation residue of non-stick wheel modified emulsified asphalt with different formulations with stabilizer B added are shown in Table 10. All the schemes in Table 10 meet the requirements for penetration in the "Technical Guide for the Construction of Non-stick Wheel Emulsified Asphalt Tack Coat".

[0052] Table 10 Penetration results of evaporation residue of non-stick wheel modified emulsified asphalt

[0053] Table 11 Analysis of variance table for penetration results of evaporation residue

[0054] The test results of the penetration of different schemes in Table 10 were analyzed by variance, and the results are shown in Table 11. R 2 = 0.999, <0.05 (the probability that the result is caused by random error is less than 5%), <0.01 (the result is more reliable, and the random error probability is less than 1%). It can be seen that the content of the rutting resistance masterbatch has a significant impact on the penetration of the evaporation residue, and the impact of the emulsifier content is relatively small. From the F value and the significance value, the influence effects of the three factors are: rutting resistance masterbatch content > emulsifier content > stabilizer B content.

[0055] The softening point results of the evaporation residues of the non-sticking wheel modified emulsified asphalt with different formulations adding stabilizer A are shown in Table 12. The requirement for the softening point of the non-sticking wheel emulsified asphalt in the "Technical Guide for the Construction of the Non-sticking Wheel Emulsified Asphalt Tack Coat" is higher than 65 °C, and all nine test schemes meet the requirements.

[0056] Table 12 Softening Point Results of the Evaporation Residues of the Non-sticking Wheel Modified Emulsified Asphalt

[0057] Table 13 Variance Analysis Table of the Softening Point Results of the Evaporation Residues

[0058] The test results of the softening point of different schemes in Table 12 were analyzed by variance, and the results are shown in Table 13. It can be seen that the content of the rutting resistance masterbatch has a significant impact on the softening point of the evaporation residue, and the impacts of the emulsifier content and the stabilizer A content are relatively less obvious. According to the significance value, the influence effects of the three factors are: rutting resistance masterbatch content > emulsifier content > stabilizer A content.

[0059] The softening point test results of the evaporation residues of different formulations of the non-sticking wheel modified emulsified asphalt adding stabilizer B are shown in Table 14. All nine test schemes meet the requirements for the softening point of the non-sticking wheel emulsified asphalt in the "Technical Guide for the Construction of the Non-sticking Wheel Emulsified Asphalt Tack Coat".

[0060] Table 14 Softening Point Results of the Evaporation Residues of the Non-sticking Wheel Modified Emulsified Asphalt

[0061] Table 15 Variance Analysis Table of the Softening Point Results of the Evaporation Residues

[0062] The test results of the softening points of different formulations in Table 14 were analyzed by variance, and the results are shown in Table 15. It can be seen that the dosage of the anti-rutting masterbatch has a significant effect on the softening point of the evaporation residue, while the dosages of the emulsifier and stabilizer B have relatively less obvious effects. According to the significance values, the influence effects of the three factors are: dosage of anti-rutting masterbatch > dosage of emulsifier > dosage of stabilizer B.

[0063] The 1-day storage stability results of different formulations of the non-stick wheel modified emulsified asphalt with stabilizer A added are shown in Table 16, and all nine schemes meet the relevant requirements in the Specification "Construction Technical Guide for Non-stick Wheel Emulsified Asphalt Tack Coat".

[0064] Table 16 1-day storage stability results of non-stick wheel modified emulsified asphalt

[0065] Table 17 Variance analysis table of 1-day storage stability results of non-stick wheel modified emulsified asphalt

[0066] The test results of the 1-day storage stability of the non-stick wheel modified emulsified asphalt with different schemes in Table 16 were analyzed by variance, and the results are shown in Table 17. R 2 = 0.992, < 0.05, < 0.01. The 1-day storage stability represents the storage resistance of the emulsified asphalt, and the lower the value, the better the storage resistance. It can be seen from Table 17 that the influence degrees of the three factors on the 1-day storage stability of the non-stick wheel modified emulsified asphalt are different. Among them, the dosages of the anti-rutting masterbatch and stabilizer A have significant effects, and their significance values are 0.0019 and 0.013 respectively, both less than 0.05. The non-stick wheel modified emulsified asphalt is a stable emulsion formed by dispersing asphalt in water through a surfactant (emulsifier) in the aqueous phase, and the main function of the stabilizer is to enhance the stability of the emulsion and prevent the non-stick wheel modified emulsified asphalt from delaminating, settling or aggregating during storage. The stabilizer can improve the stability of the emulsion and have a significant impact on the storage stability. An excessive dosage of the anti-rutting masterbatch will cause a significant increase in the softening point of the non-stick wheel modified emulsified asphalt, which is not conducive to emulsification and at the same time reduces the storage stability of the non-stick wheel modified emulsified asphalt. The influence degrees of the three factors on the 1-day storage stability are: dosage of stabilizer A > dosage of anti-rutting masterbatch > dosage of emulsifier.

[0067] The 1-day storage stability results of different formulations of the non-stick wheel modified emulsified asphalt with stabilizer B added are shown in Table 18, and all nine schemes meet the relevant requirements in the Specification "Construction Technical Guide for Non-stick Wheel Emulsified Asphalt Tack Coat".

[0068] Table 18 1-day stability results table of non-stick wheel modified emulsified asphalt

[0069] Table 19 ANOVA Table of 1d Stability Results of Non-stick Wheel Modified Emulsified Asphalt

[0070] The test results of the 1d storage stability of the non-stick wheel modified emulsified asphalt with different schemes in Table 18 were analyzed by variance, and the results are shown in Table 19. R 2 = 0.887, <0.05, <0.01. The influence degrees of the three factors on the 1d storage stability of the non-stick wheel modified emulsified asphalt are different. The influence degrees of the three factors on the 1d storage stability are as follows: dosage of stabilizer B > dosage of anti-rutting masterbatch > dosage of emulsifier.

[0071] The 5d storage stability results of different formulations of non-stick wheel modified emulsified asphalt added with stabilizer A are shown in Table 20. The requirement of the "Technical Guide for the Construction of Non-stick Wheel Emulsified Asphalt Tack Coat" is that the 5d storage stability < 5%. It can be seen that Scheme 8 in Table 14 does not meet the corresponding requirements, and the other schemes all meet the requirements.

[0072] Table 20 5d Stability Results Table of Non-stick Wheel Modified Emulsified Asphalt

[0073] Table 21 ANOVA Table of 5d Stability Results of Non-stick Wheel Modified Emulsified Asphalt

[0074] The test results of the 5d storage stability of different schemes of non-stick wheel modified emulsified asphalt in Table 20 were analyzed by variance, and the results are shown in Table 21. R 2 = 0.990, <0.05, <0.01. It can be seen that the dosages of the anti-rutting masterbatch and stabilizer A have significant influence effects, and the significance values of the two are 0.019 and 0.023 respectively, both less than 0.05. The influence degrees of the three factors on the 5d storage stability are as follows: dosage of anti-rutting masterbatch > dosage of stabilizer A > dosage of emulsifier.

[0075] The 5d storage stability results of different formulations of non-stick wheel modified emulsified asphalt added with stabilizer B are shown in Table 22, and all nine schemes meet the requirements of the "Technical Guide for the Construction of Non-stick Wheel Emulsified Asphalt Tack Coat" for the 5d storage stability.

[0076] Table 22 5d Stability Results Table of Non-stick Wheel Modified Emulsified Asphalt

[0077] Table 23 Variance analysis table of 5d stability results of non-stick wheel modified emulsified asphalt

[0078] The test results of the 5d storage stability of different schemes of non-stick wheel modified emulsified asphalt in Table 22 were analyzed by variance, and the results are shown in Table 23. R 2 = 0.997, <0.05, <0.01. It can be seen that the dosages of the rutting resistance masterbatch and stabilizer B have significant effects, and the significance values of the two are 0.047 and 0.003 respectively, both less than 0.05. The influence degrees of the three factors on the 5d storage stability are as follows: dosage of stabilizer B > dosage of rutting resistance masterbatch > dosage of emulsifier.

[0079] According to the previous research, with the increase of the dosage of the rutting resistance masterbatch, the softening point of the non-stick wheel modified emulsified asphalt continuously rises and the penetration continuously decreases. When the dosage of the rutting resistance masterbatch reaches more than 25%, the softening point can reach above 65℃ and the penetration is lower than 40mm, both meeting the requirements of the "Construction Technical Guide for Non-stick Wheel Emulsified Asphalt Tack Coat".

[0080] The storage stability becomes better with the increase of the dosage of the stabilizer, but too much stabilizer has little effect on the storage stability. Individual schemes have met the requirements when using a low dosage of the stabilizer. In order to save costs, the dosage of the stabilizer should be as low as possible under the condition that the storage stability of the emulsified asphalt meets the requirements. Therefore, when the dosage of the rutting resistance masterbatch is 40%, the dosage of stabilizer A is determined to be 0.2%. When the dosages of the rutting resistance masterbatch are 30% and 20%, stabilizer A with a dosage of 0.1% is used. When the dosage of stabilizer B is 0.1%, the storage stability requirements can be well met. Therefore, stabilizer B with a dosage of 0.1% is used under different dosages of the rutting resistance masterbatch.

[0081] The aforementioned test results show that the emulsifier has no significant effect on the penetration, softening point and storage stability of the evaporation residue, because its main function is to provide the connection between asphalt and water. When the dosage of the emulsifier is 6%, the hard asphalt can be emulsified and the stability of the emulsified asphalt also meets the requirements. When the dosage of the emulsifier is 7%, the stability effect is relatively better. However, if the dosage of the emulsifier is too much, it may cause the problem of secondary emulsification and the cost is relatively high. Therefore, the dosage of the emulsifier is preferably 6%.

[0082] Based on the above test results, a preliminary optimized formula of non-stick wheel modified emulsified asphalt as shown in Table 24 is proposed, and subsequent performance tests are carried out to determine the final optimized formula.

[0083] Table 24 Preliminary optimized formula of non-stick wheel modified emulsified asphalt

[0084] Viscosity is a very important index reflecting the road performance of road asphalt materials. Macroscopically, viscosity is the ability of asphalt to resist fluid flow, and microscopically, it is the internal friction formed by the gravitational force between the internal molecular structures of asphalt. There are many types of viscosity, such as standard viscosity, dynamic viscosity, kinematic viscosity, etc. Among them, the dynamic viscosity at 60°C is an important parameter reflecting the high-temperature permanent deformation resistance ability of road asphalt. At the same time, the Engler viscosity at 25°C is an important index used to measure the fluidity and viscosity of emulsified asphalt at normal temperature. The higher the Engler viscosity of emulsified asphalt, the poorer its fluidity, the greater the flow resistance, and the higher the viscosity. This usually means that a greater external force is required for the emulsified asphalt to be paved during construction, which affects the construction efficiency. On the contrary, emulsified asphalt with a lower Engler viscosity usually has better fluidity and is convenient for paving during road construction. Therefore, the 60°C dynamic viscosity of the evaporation residue of non-stick wheel modified emulsified asphalt in Schemes 1 - 6 and the 25°C Engler viscosity of non-stick wheel modified emulsified asphalt were tested, and the test results are shown in Table 25.

[0085] Table 25 Test results of dynamic viscosity and Engler viscosity of non-stick wheel modified emulsified asphalt

[0086] The results in Table 25 show that the 60°C dynamic viscosity of all schemes is significantly higher than 5000 Pa·s, indicating that these non-stick wheel modified emulsified asphalts have strong high-temperature deformation resistance ability, can bond well with the road surface, and effectively prevent the occurrence of diseases such as interlayer slip and delamination. At the same time, the 25°C Engler viscosity of all schemes is within the range of 1 - 30, meeting the relevant requirements of the "Construction Technology Guide for Non-Stick Wheel Emulsified Asphalt Tack Coat", indicating that these non-stick wheel modified emulsified asphalts have good fluidity at normal temperature and can meet the operational requirements during construction.

[0087] In comparison, the 25°C Engler viscosity of Schemes 4, 5, and 6 is significantly higher than that of Schemes 1, 2, and 3, indicating that the formula of non-stick wheel modified emulsified asphalt added with Stabilizer B (HVS asphalt stabilizer) has a higher viscosity at normal temperature, while the formula of non-stick wheel modified emulsified asphalt added with Stabilizer A (Shanxi emulsified asphalt enhancer) has better fluidity at normal temperature, which is more beneficial for laying and operation during construction.

[0088] In summary, the non-stick wheel modified emulsified asphalt of all schemes has good performance at high temperature, but there are differences in fluidity at normal temperature. It is necessary to select a suitable formula according to different construction requirements to ensure the realization of the dual goals of construction efficiency and road surface performance.

[0089] The technical indicators of the non-sticking wheel modified emulsified asphalt for each scheme were tested and analyzed, and the results are shown in Tables 26 to 31. It can be seen that the non-sticking wheel modified emulsified asphalt of Schemes 1-6 all meet the requirements of the Technical Guide for the Construction of the Tack Coat of Non-sticking Wheel Emulsified Asphalt.

[0090] Table 26 Technical Index Table of Scheme 1

[0091] Table 27 Technical Index Table of Scheme 2

[0092] Table 28 Technical Index Table of Scheme 3

[0093] Table 29 Technical Index Table of Scheme 4

[0094] Table 30 Technical Index Table of Scheme 5

[0095] Table 31 Technical Index Table of Scheme 6

[0096] In the project research, the pull-out strength of the composite plate specimen at 25 °C was used as the evaluation index to determine the optimal dosage of the non-sticking wheel modified emulsified asphalt as the bonding layer material. In the specific test, non-sticking wheel modified emulsified asphalt with three dosages of 0.4 kg / m 2 , 0.7 kg / m 2 , and 1.0 kg / m 2 were respectively coated between the AC-20 and AC-13 layers to carry out the pull-out test. A servo hydraulic press with a range of 100 kN was used for the pull-out test. The test loading rate was set at 50 mm / min, and the test end condition was set as the loading force dropped to 5% of the maximum load. Each group of specimens was subjected to 3 parallel tests, and the final result was the average value.

[0097] Composite plate specimens were made from the non-sticking wheel modified emulsified asphalt with six determined formulations at three spraying dosages, and the pull-out strength test was carried out at 25 °C. The results are shown in Table 32.

[0098] Table 32 Pull-out Strength Table of Composite Plate Specimens with Three Spraying Dosages of Modified Emulsified Asphalt with Different Formulations

[0099] As can be seen from Table 32, with the increase in the dosage of the non-sticking wheel modified emulsified asphalt between AC-13 and AC-20 layers, the draw strength shows a trend of first increasing and then decreasing with the dosage. Analyzing the reasons, when the dosage of the non-sticking wheel modified emulsified asphalt is small, there is also less asphalt after demulsification, and it is difficult to form a complete asphalt film on the surface of the mixture, resulting in a small interlayer bonding force. With the increase in the dosage of the non-sticking wheel modified emulsified asphalt, a relatively complete asphalt film is formed in the upper and lower structural layers. At this time, the draw strength between layers is jointly borne by the bonding force of the asphalt and the frictional resistance between the upper and lower layers, so the draw strength increases. When the dosage exceeds a certain value, too much asphalt will slide freely between the upper and lower layers, making it easier for the upper and lower layers to slide relative to each other. Therefore, it is recommended that the optimal dosage of the non-sticking wheel emulsified asphalt be 0.7 kg / m 2 or so.

[0100] Furthermore, ordinary emulsified asphalt and SBR modified emulsified asphalt are used as control groups, and the interlayer draw strength characteristics of the six formulated non-sticking wheel modified emulsified asphalts developed in this project are compared at different temperatures, with the spreading amount being 0.7 kg / m 2 . The test results of the draw strength of different tack coat materials at each temperature are as Figure 4 shown.

[0101] From Figure 4 the results in it, it can be seen that at 25°C and 40°C, the draw strength of the non-sticking wheel modified emulsified asphalt of this application: non-sticking wheel emulsified asphalt > SBR modified emulsified asphalt > matrix emulsified asphalt. The dosages of the rutting resistance masterbatch in Schemes 1-3 are 25%, 30%, and 40% respectively, and the dosages of the rutting resistance masterbatch in Schemes 4-6 are 25%, 30%, and 40%. It can be seen that with the continuous increase in the dosage of the rutting resistance masterbatch, at 25°C, the draw strength of Schemes 1-6 is increased by 207%-355% compared with ordinary emulsified asphalt, and the draw strength is increased by 139%-254% compared with SBR modified emulsified asphalt. At 40°C, the draw strength of Schemes 1-6 is increased by 337%-610% compared with ordinary emulsified asphalt, and the draw strength is increased by 196%-404% compared with SBR modified emulsified asphalt. By analyzing the draw strength ratio of different interlayer bonding materials, it is found that the draw strength ratio of the non-sticking wheel modified emulsified asphalt at 25°C and 40°C is 60%-75% of SBR, the draw strength ratio of the SBR modified emulsified asphalt at 25°C and 40°C is 51.9%, and the draw strength ratio of the ordinary emulsified asphalt is 45.2%. The draw strength ratio of the non-sticking wheel modified emulsified asphalt is relatively high compared with other interlayer materials. It shows that the tensile draw strength of the non-sticking wheel emulsified asphalt as an interlayer material is less affected by temperature changes, and the amplitude of the interlayer bonding performance changing with temperature is relatively small, while the SBR modified emulsified asphalt and the matrix emulsified asphalt are more affected by temperature. Therefore, the non-sticking wheel modified emulsified asphalt of this application has good temperature stability as an interlayer bonding material.

[0102] To better investigate the shear resistance performance of the tack coat, a direct shear test was carried out. The forming method of the composite plate specimens was the same as that of the pull-out test. Non-stick wheel modified emulsified asphalt with dosages of 0.4 kg / m 2 , 0.7 kg / m 2 , and 1.0 kg / m 2 was respectively applied to the AC-20 and AC-13 structural layers. A servo-hydraulic press with a measuring range of 100 kN was used for the direct shear test. The test loading rate was set at 10 mm / min, and the test temperature was 25 °C. The shear strengths of each tack coat material at each spreading dosage are shown in Table 5. As Figure 5 can be seen, from the perspective of the dosage of non-stick wheel modified emulsified asphalt, with the increase of the spreading dosage, the interlayer shear strength shows a trend of first increasing and then decreasing with the dosage. Analyzing the reason, when the dosage of non-stick wheel emulsified asphalt is small, there is also less asphalt after demulsification, and it is difficult to form a complete asphalt film on the surface of the mixture, resulting in a small bonding force. At this time, the shear strength is mainly borne by the frictional resistance between the upper and lower layers. With the increase of the dosage, a complete asphalt film is formed in the structure, and the shear strength at this time is jointly borne by the bonding force of the tack coat asphalt and the frictional resistance between the upper and lower layers, so the shear strength becomes larger. When the dosage exceeds the appropriate value, too much asphalt will slide freely between the upper and lower layers, making it easier for the upper and lower layers to have relative sliding. Therefore, it is recommended that the optimal spreading dosage of non-stick wheel modified emulsified asphalt is 0.7 kg / m 2 .

[0103] In the direct shear test, the failure form of the specimens was the fracture within the asphalt mixture layer, not the interlayer failure. Since the AC-20 asphalt mixture in the lower layer used 70# Xinhai asphalt with a relatively low softening point, it was more likely to be damaged under the test conditions of 60 °C. The non-stick wheel modified emulsified asphalt used in the interlayer could form a strong interlayer bond, causing the internal mixture of the lower layer to fail prior to the interlayer failure, which also indirectly reflects that the non-stick wheel modified emulsified asphalt developed in this project can provide good interlayer shear strength as an interlayer bonding material. Further, ordinary emulsified asphalt and SBR modified emulsified asphalt were used as control groups to compare the interlayer shear strength characteristics at different temperatures with the six formulated non-stick wheel modified emulsified asphalts developed in this project. The spreading dosage was 0.7 kg / m 2 . The test results of the shear strengths of different tack coat materials at each temperature are as Figure 6 shown.

[0104] From Figure 6From the results, it can be seen that at 25°C and 45°C, the shear strength of the non-stick wheel modified emulsified asphalt of this application is: non-stick wheel emulsified asphalt > SBR modified emulsified asphalt > matrix emulsified asphalt. The dosages of the rutting resistance masterbatch in Schemes 1-3 are 25%, 30%, and 40% respectively, and the dosages of the rutting resistance masterbatch in Schemes 4-6 are 25%, 30%, and 40%. It can be seen that as the dosage of the rutting resistance masterbatch increases, its shear strength also increases. At 25°C, the shear strength of Schemes 1-6 is increased by 116%-200% compared with that of ordinary emulsified asphalt, and the shear strength is increased by 89%-162% compared with that of SBR modified emulsified asphalt. At 40°C, the shear strength of Schemes 1-6 is increased by 129%-284% compared with that of ordinary emulsified asphalt, and the shear strength is increased by 87%-213% compared with that of SBR modified emulsified asphalt. By analyzing the shear strength ratio of different interlayer bonding materials, it is found that the shear strength ratio of the non-stick wheel modified emulsified asphalt at 25°C and 40°C is 67%-84%, the shear strength ratio of the SBR modified emulsified asphalt at 25°C and 40°C is 67.9%, and the shear strength ratio of the ordinary emulsified asphalt at 25°C and 40°C is 63.3%. The shear strength ratio of the non-stick wheel modified emulsified asphalt is relatively high compared with other interlayer materials. It shows that the shear strength of the non-stick wheel modified emulsified asphalt as an interlayer material is less affected by temperature changes, and the amplitude of the interlayer bonding performance changing with temperature is relatively small, while the SBR modified emulsified asphalt and the matrix emulsified asphalt are more affected by temperature. Therefore, the non-stick wheel modified emulsified asphalt of this application has good temperature stability as an interlayer bonding material.

[0105] Referring to the non-stick wheel detection method in the Japanese emulsified asphalt specification, select a rutting plate with a flat surface, and uniformly apply the non-stick wheel modified emulsified asphalt, ordinary matrix emulsified asphalt (i.e., the matrix in Figures 7 to 10 ), and SBR modified emulsified asphalt (i.e., the SBR in Figures 7 to 10 ) three bonding materials on the surface of the rutting plate according to the spreading amount of 0.4 kg / m 2 , 0.7 kg / m 2 , and 1.0 kg / m 2 . Apply according to the plane area of the wheel. The plane size is 5 cm × 30 cm, so the area is 0.015 m 2。After the tack coat material (non-stick wheel modified emulsified asphalt, ordinary matrix emulsified asphalt) is sprayed, it is left to demulsify at room temperature. After demulsification, the rutting plate is placed in the rutting tester for 4 h. Considering the error in the temperature when the rutting tester is turned on, the temperature is controlled at 60 °C ± 5 °C. After the rutting specimen is fully insulated, a piece of A4 paper that can fully absorb the asphalt material is placed on the rutting specimen. To prevent the white paper from being taken away by the wheel, a cardboard is placed between the white paper and the wheel. The rutting tester is started, and it is rolled 1 time, 5 times, 10 times, and 20 times to simulate the situation of repeated rolling of the wheels during on-site construction. The mass of the asphalt adhered is obtained from the mass difference of the A4 paper before and after rolling, and the adhesion rate of the asphalt (non-stick wheel modified emulsified asphalt, ordinary matrix emulsified asphalt) after demulsification is calculated. The calculation formula is as follows: 。

[0106] In the formula, m2 is the mass of the A4 paper after rolling, m1 is the mass of the A4 paper before rolling, S is the area coated with asphalt, and D is the spraying amount of the bonding material.

[0107] At a spraying amount of 0.4 kg / m 2 The results of the non-stick wheel test are as follows Figures 7 to 10 shown. After 1 cycle, 5 cycles, 10 cycles, and 20 cycles of wheel rolling, the adhesion rate of the non-stick wheel modified emulsified asphalt of the present application is much smaller than that of the ordinary matrix emulsified asphalt. At the same number of rolling times, the adhesion rate of the non-stick wheel modified emulsified asphalt is reduced by 71.1% - 94.2% compared with the ordinary matrix emulsified asphalt, and is reduced by 64.5% - 92.5% compared with the SBR modified emulsified asphalt. The decrease is the most significant when rolling 1 time (up to 92.5%). Analyzing the reasons, the anti-rutting masterbatch is added in Schemes 1 - 6, which improves the softening point of the non-stick wheel modified emulsified asphalt and significantly improves the non-stick wheel property. Comparing Schemes 1, 2, and 3, as the dosage of the anti-rutting masterbatch increases, the adhesion rate of the corresponding prepared non-stick wheel modified emulsified asphalt decreases significantly. The same rule is shown in Schemes 4, 5, and 6, indicating that increasing the dosage of the anti-rutting masterbatch helps to improve the non-stick wheel property of the non-stick wheel modified emulsified asphalt. The adhesion rates of Schemes 1 and 4 are significantly higher than those of other schemes, because the dosage of the anti-rutting masterbatch added in Schemes 1 and 4 is 25%, which is less than that of other schemes, and its softening point is only about 65 °C, and the wheel sticking effect is relatively more obvious than other schemes under the test condition of 60 °C.

[0108] To further determine the optimal construction temperature of the tack coat oil, with a fixed spraying amount of 0.7 kg / m², non-stick wheel tests are carried out for Schemes 2, 3, 5, and 6 under three spraying temperature conditions of 50 °C, 60 °C, and 70 °C. It is rolled back and forth 10 times, and the mass changes of the A4 paper before and after the test are recorded, and the mass of the adhered asphalt and the adhesion rate are calculated. The test results at different temperatures are as follows Figure 11As shown. It can be seen that when the four kinds of non-sticking wheel modified emulsified asphalt of Scheme 2, Scheme 3, Scheme 5, and Scheme 6 are used as tack coats, with the increase of the spraying temperature, both the asphalt quality adhered to the wheels and the calculated adhesion rate index show an upward trend. The same rule also applies to ordinary matrix emulsified asphalt and SBR modified emulsified asphalt, and the asphalt quality and adhesion rate adhered by the four developed non-sticking wheel modified emulsified asphalt are significantly lower than those of ordinary matrix emulsified asphalt and SBR modified emulsified asphalt.

[0109] In addition, when the temperature rises from 50°C to 60°C, the increase in the adhesion rate of the four schemes is relatively small (0.2% - 1%). However, when the temperature rises from 60°C to 70°C, the increase in the adhesion rate of each scheme is obvious (2.8% - 4.1%), indicating that the non-sticking wheel property of the non-sticking wheel modified emulsified asphalt tack coat significantly decreases when the spraying temperature is higher than 60°C. Based on the above test results, from the perspective of improving the interlayer bonding force and having excellent non-sticking wheel properties at the same time, the optimal construction temperature of the non-sticking wheel modified emulsified asphalt of this application is 60°C.

[0110] The above embodiments are only used to illustrate the technical solutions of this application, rather than limiting this application; although this application has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that: they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of this application.

Claims

1. A preparation method of non-stick wheel modified emulsified asphalt, characterized in that, Comprising: Mix the rutting-resistant masterbatch with the asphalt matrix and grind to obtain modified asphalt, and place the modified asphalt in a constant-temperature oven and keep it at the first temperature; wherein, the dosage of the rutting-resistant masterbatch is 25%-40%; Mix the emulsifier, stabilizer and water, and heat and stir to obtain an emulsion at the second temperature; Add an acidic solution to the emulsion until the pH of the emulsion is adjusted to the set pH range; Introduce the emulsion into a colloid mill, and slowly pour the modified asphalt at the first temperature into the colloid mill to obtain non-sticking-wheel modified emulsified asphalt.

2. The method according to claim 1, wherein The first temperature is 170°C.

3. The method according to claim 1, wherein The second temperature is 65-70°C.

4. The method according to claim 1, characterized in that, The set pH range is 2-3.

5. The method according to claim 1, wherein The acidic solution is hydrochloric acid solution.

6. The method according to claim 1, wherein The step of slowly pouring the modified asphalt at the first temperature into the colloid mill further includes: When the color of the emulsion in the colloid mill changes, increase the pouring speed of the modified asphalt.

7. The method according to claim 1, characterized in that, The stabilizer includes Shanxi emulsified asphalt enhancer and HVS asphalt stabilizer; When the dosage of the rutting-resistant masterbatch is 40%, the dosage of Shanxi emulsified asphalt enhancer is 0.2%; When the dosage of the rutting-resistant masterbatch is 20%-30%, the dosage of Shanxi emulsified asphalt enhancer is 0.1%; The dosage of HVS asphalt stabilizer is 0.2%.

8. The method according to claim 1, characterized in that The step of mixing the emulsifier, stabilizer and water includes: The emulsifier is E106, and when adding the emulsion to prepare the non-sticking-wheel modified emulsified asphalt, the dosage of the emulsifier is 6%.

9. The method according to claim 1, wherein After obtaining the non-sticking-wheel modified emulsified asphalt by mixing, it further includes: Rapidly cool the non-sticking-wheel modified emulsified asphalt to prevent high-temperature demulsification of the non-sticking-wheel modified emulsified asphalt.

10. A non-stick wheel modified emulsified asphalt prepared by the method according to any one of claims 1-9, characterized in that, Comprising: The spraying amount of the non-stick wheel modified emulsified asphalt is 0.7 kg / m 2 , and the construction temperature is 60°C.